Achieving Sustainable Livelihood in Cold Arid Regions of India through Multienterprise Options - Bhatt, R. Bhatt K; Raghuvanshi, M. S; Kalia, Rajwant K (Annals of Arid Zone, 2016)
The cold arid zone of India being located in the rain shadow of Himalayas is one of the driest regions in the world. The area remains inaccessible to the outside world for nearly six months in a year due to heavy snowfall. This fragile ecosystem with limited availability of natural resources is a growing attraction for tourists. Multi-enterprise option needs to be strengthened for the upliftment of the socio-economic status of the region. Integrated farming systems combining fruit and fodder trees with medicinal plants into the cropping system can address the problems of conservation of medicinal plants as well as can ensure assured income to the farmers. Organic farming, protected cultivation, off season vegetable production, value addition and development of better storability methods for vegetables and fruits will be remunerative to the farmers of cold arid region. Animal husbandry is another important component of subsistence agriculture. The Ladakhis raise cattle, sheep, goats, horses and Dzo (cross between yak and cow), as primary source of milk, meat, wool and other byproducts. Mostly sheep and goats are reared for wool, milk and meat purpose. Pashmina and Changthangi goats are reared for fine grade Pashmina wool. Cold water fish production has emerged as an additional source of income generation in the region. Tourism is also emerging as an important source of economy providing jobs to thousands of people. Strengthening of all such enterprises can ensure livelihood security to the local population of cold arid region in addition to conservation of this unique ecosystem and cultural heritage. Keywords: Cold arid zone,